Swim, duck, swim! - Lurie, Susan; Head, Murray 1939- (New York, N.Y. Feiwel and Friends, 2014)
A photographic tale about Duckling the reluctant swimmer finds him resenting the pressure exerted by his patient Mama and Papa Duck, preferring to stay dry and take a nap before eventually deciding to join his siblings in the pond.
Keywords: Ducks; Swimming; Stories in rhyme; Ducks; Swimming; Stories in rhyme; Picture books for children; Ducks; Stories in rhyme; Swimming; Fiction; Juvenile works